Ageing – Oxidative stress, PTMs and disease. (August 2022) - Ebert, Thomas; Tran, Ngoc; Schurgers, Leon; Stenvinkel, Peter; Shiels, Paul G.
Abstract: Post-translational modifications (PTMs) have been proposed as a link between the oxidative stress-inflammation-ageing trinity, thereby affecting several hallmarks of ageing. Phosphorylation, acetylation, and ubiquitination cover >90% of all the reported PTMs. Several of the main PTMs are involved in normal "healthy" ageing and in different age-related diseases, for instance neurodegenerative, metabolic, cardiovascular, and bone diseases, as well as cancer and chronic kidney disease. Ultimately, data from human rare progeroid syndromes, but also from long-living animal species, imply that PTMs are critical regulators of the ageing process. Mechanistically, PTMs target epigenetic and non-epigenetic pathways during ageing. In particular, epigenetic histone modification has critical implications for the ageing process and can modulate lifespan. Therefore, PTM-based therapeutics appear to be attractive pharmaceutical candidates to reduce the burden of ageing-related diseases. Several phosphorylation and acetylation inhibitors have already been FDA-approved for the treatment of other diseases and offer a unique potential to investigate both beneficial effects and possible side-effects. As an example, the most well-studied senolytic compounds dasatinib and quercetin, which have already been tested in Phase 1 pilot studies, also act as kinase inhibitors, targeting cellular senescence and increasing lifespan. Future studies need to carefully determine the best PTM-based candidates for the treatment of the "diseasome of ageing". Highlights: Post-translational modifications (PTMs) link oxidative stress and ageing. Data from progeroid syndromes and long-living animals implicate PTMs in the ageing process. PTMs are highly relevant for the epigenetic regulation of ageing and related diseases. Phosphorylation and acetylation inhibitors are therapeutic targets in ageing.